2019
DOI: 10.7759/cureus.5387
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Hypernatremia Due to Pure Dehydration Could Be a Potential Risk Factor for Transient Atrial Fibrillation

Abstract: Although atrial fibrillation (AF) has been correlated with hyponatremia, it has not been described in association with the correction of chronic hypernatremia in previous studies.Here, we describe three elderly patients who had hypernatremia on presentation, most likely secondary to dehydration. Their electrocardiogram (EKG) on presentation was normal, and they had no known history of AF but developed transient AF during the course of hypernatremia correction. Similar occurrences have not been reported previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Our patient appropriately responded to exogenous administration of desmopressin, suggesting probable feedback inhibition on the release of ADH due to vasopressin infusion. Nevertheless, it is important to be aware of these manifestations as fluctuations in serum sodium are associated with morbidity, including neurological dysfunction and atrial fibrillation [ 16 ]. Furthermore, increased urine output may affect the estimation of GFR and may result in suboptimal antimicrobial dosing [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our patient appropriately responded to exogenous administration of desmopressin, suggesting probable feedback inhibition on the release of ADH due to vasopressin infusion. Nevertheless, it is important to be aware of these manifestations as fluctuations in serum sodium are associated with morbidity, including neurological dysfunction and atrial fibrillation [ 16 ]. Furthermore, increased urine output may affect the estimation of GFR and may result in suboptimal antimicrobial dosing [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we noticed that the best strategy is to use the OPL and MCS using ISNR as explained in section 4. The proposed protocol offers 1.8 dB gain with respect to optimal MCS and FPL as considered in [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Fixed Packet Length N=350 : AMC using ASNR Fixed Packet Length N=590 : AMC using ASNR Fixed Packet Length N=1190 : AMC using ASNR Optimal packet length : AMC using ASNR Adaptive packet Length and Adaptive MCS using ISNR Fixed packet length and adaptive MCS using INSR Figure 10: Throughput of MIMO systems with AMC using ASNR or ISNR : fixed versus OPL.…”
Section: Theoretical and Simulation Resultsmentioning
confidence: 99%
“…The relationship between hypernatremia and adverse prognosis could be due to decreased left ventricular contractility ( 36 ) and/or increased peripheral insulin resistance ( 37 ). A case report showed that three hypernatremic patients incurred AF during treatment for hypernatremia ( 38 ). It is possible that hypernatremia could be a risk factor for AF-related mortality because of atrial stretch during treatment-stimulated pulmonary vein electrical activity ( 39 ).…”
Section: Discussionmentioning
confidence: 99%